PENGEMBANGAN BAHAN AJAR MEMBACA KRITIS TEKS SASTRA UNTUK PELAJAR BIPA TINGKAT MAHIR - Wika Nurma Hidayatul Nafi'ah; Suyitno, Imam; Andajani, Kusubakti (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
The research and development of literary text-based reading teaching materials for advanced BIPA learners was motivated by the results of a preliminary study that showed the potential of literary texts as reading learning materials in advanced BIPA classes. This study aims to produce teaching materials that meet the requirements of content feasibility, presentation systematics, language, and appearance so that they can help train critical reading skills for BIPA learners. The research model used is the 4D model by Thiagarajan, et al., involving test subjects in the form of BIPA material experts, teaching material preparation experts, design experts, practitioners (advanced BIPA teachers), and advanced BIPA students. The data obtained through the validation test shows that this teaching material is classified as very feasible and ready to be implemented with a percentage of feasibility reaching 89.1%. However, through the limited field test, there were several aspects that required revision to increase the percentage of feasibility to 83.3%. Nevertheless, this product is still feasible to be implemented with minor revisions. This teaching material can be utilized by BIPA students as an enrichment material in practicing critical reading skills by utilizing literary texts. Advanced level BIPA teachers can also use this teaching material to teach reading skills to students and introduce the works of Indonesian writers. BIPA researchers and activists are advised to consider this teaching material as a reference in developing literary text-based reading teaching materials that are still not widely available.